A Validated Simultaneous Estimation of Amlodipine and Olmesartan in Tablet Dosage form by using RP-HPLC - Samba Siva Rao Bodavula; Dr. Amitkumar Janardan Raval (International Journal of Pharma and Bio Sciences, 2020)
A new, simple, accurate, precise and reproducible reverse phase high performance liquid chromatography method was developed and fully validated for the simultaneous estimation of amlodipine besylate, olmesartan medoxamil in tablet dosage form isocratically using acetonitrile: methanol: phosphate buffer pH-3.0 (48:12:40 Percentage v/v/v) as mobile phase and Prontosil C-18 column (4.6 x 250 mm, 5 μ particle size) as stationary phase and chromatogram was recorded at 232 nm at a flow rate of 1.2 mL/min. The developed method was validated by measuring the linearity, precision, the limit of detection (LOD), robustness and ruggedness, drug recovery, and the system suitability parameters. The objective of the current study was to develop a simple, accurate, precise and rapid RP-HPLC method with subsequent validation as per ICH guidelines for the determination of Amlodipine (AML) and Olmesartan (OLM) using mobile phase containing a mixture of acetonitrile and methanol in the ratio of 60:40 as the solvent. Main principle involved in the present method was determining the retention time at wavelength of 260 nm. The retention time of AML and OLM was found to be 3.3 and 1.8 minutes respectively. The linearity of the proposed method was investigated in the range of 5-25 µg/ml (r2 = 0.9999) for AML and 10-50 µg/ml (r2 = 0.9998) for OLM respectively. The method was statistically validated for its linearity, accuracy, and precision. The measured parameters indicate the developed method is useful in the determination of AML and OLM in pure and tablet dosage form.